Gallbladder polyps: Correlation of size and clinicopathologic characteristics based on updated definitions - BAĞCI ÇULÇİ, PELİN (PUBLIC LIBRARY SCIENCE, 2020)
Background Different perspectives exist regarding the clinicopathologic characteristics, biology and management of gallbladder polyps. Size is often used as the surrogate evidence of polyp behavior and size of >= 1cm is widely used as cholecystectomy indication. Most studies on this issue are based on the pathologic correlation of polyps clinically selected for resection, whereas, the data regarding the nature of polypoid lesions from pathology perspective -regardless of the cholecystectomy indication- is highly limited. Methods In this study, 4231 gallbladders -606 of which had gallbladder carcinoma- were reviewed carefully pathologically by the authors for polyps (defined as >= 2 mm). Separately, the cases that were diagnosed as gallbladder polyps in the surgical pathology databases were retrieved. Results 643 polyps identified accordingly were re-evaluated histopathologically. Mean age of all patients was 55 years (range: 20-94); mean polyp size was 9 mm. Among these 643 polyps, 223 (34.6%) were neoplastic: I. Non-neoplastic polyps (n = 420; 65.4%) were smaller (mean: 4.1 mm), occurred in younger patients (mean: 52 years). This group consisted of fibromyoglandular polyps (n = 196) per the updated classification, cholesterol polyps (n = 166), polypoid pyloric gland metaplasia (n = 41) and inflammatory polyps (n = 17). II. Neoplastic polyps were larger (mean: 21 mm), detected in older patients (mean: 61 years) and consisted of intra-cholecystic neoplasms (WHO's adenomas and intracholecystic papillary neoplasms, >= 1 cm; n = 120), their incipient version (<1 cm) (n = 44), polypoid invasive carcinomas (n = 26) and non-neoplastic polyps with incidental dysplastic changes (n = 33). In terms of size cut-off correlations, overall, only 27% of polyps were >= 1 cm, 90% of which were neoplastic. All (except for one) >= 2 cm were neoplastic. However, 14% of polyps <1 cm were also neoplastic. Positive predictive value of >= 1 cm cut-off -which is widely used for cholecystectomy indication-, was 94.3% and negative predictive value was 85%. Conclusions Approximately a third of polypoid lesions in the cholecystectomies (regardless of the indication) prove to be neoplastic. The vast majority of (90%) of polyps >= 1 cm and virtually all of those >= 2 cm are neoplastic confirming the current impression that polyps >= 1 cm ought to be removed. However, this study also illustrates that 30% of the neoplastic polyps are <1 cm and therefore small polyps should also be closely watched, especially in older patients.
Keywords: PAPILLARY NEOPLASMS; RISK STRATIFICATION; LESIONS; ULTRASONOGRAPHY; MANAGEMENT; LARGER; CM